2010
DOI: 10.1111/j.1447-0756.2010.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and subsequent pregnancy outcomes in peripartum cardiomyopathy

Abstract: Subsequent pregnancies should be discouraged as it increases the risk of recurrence of left ventricular dysfunction. Anticoagulation may be considered as a primary prevention of thromboembolism in pregnant mothers with peripartum cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 15 publications
2
37
0
1
Order By: Relevance
“…173 Multidisciplinary care for patients with PPCM should include cardiologists, high-risk obstetrics and perinatologists, cardiac anesthesiologists, cardiac intensivists, and pediatricians. 158,193 Genetic predisposition can play a role in development of PPCM; therefore, in patients in whom PPCM is suspected who have a familial pattern and history, genetic testing and genetic counseling could be helpful.…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…173 Multidisciplinary care for patients with PPCM should include cardiologists, high-risk obstetrics and perinatologists, cardiac anesthesiologists, cardiac intensivists, and pediatricians. 158,193 Genetic predisposition can play a role in development of PPCM; therefore, in patients in whom PPCM is suspected who have a familial pattern and history, genetic testing and genetic counseling could be helpful.…”
Section: Diagnosismentioning
confidence: 99%
“…1,191 Mechanical circulatory support (MCS), either as temporary or bridge to transplantation, and heart transplantation have been used successfully in patients with PPCM for whom medical therapy has failed and who require continuous inotropic therapy. 1,158,[209][210][211] Given the hypercoagulable state known to exist during pregnancy, anticoagulation can be considered in patients with PPCM with severe LV dysfunction (LVEF <30%) to prevent thrombus formation, 158,174,193,212 but warfarin should not be used during pregnancy.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have reported on subsequent pregnancies of women with a history of PPCM. 31,32,33,34 Elkayam et al studied 44 women with PPCM and a subsequent pregnancy and found that LVEF increased after the index pregnancy but decreased again during the subsequent pregnancy, irrespective of earlier values. Developments of HF symptoms were more frequent in the group, where LVEF had not normalized before the subsequent pregnancy (44 vs. 21%).…”
Section: Discussionmentioning
confidence: 99%